Sodium metal negative electrode and method of making and battery

CN116613279BActive Publication Date: 2026-10-27湖州超钠新能源科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310639243.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2026-10-27
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

[0003]上述的改善钠金属负极性能的策略各有其优缺点,例如,人造SEI膜改性后的钠金属负极其能量密度几乎不降低,但是其强度大都不足以抵抗电极体积无休止的膨胀/收缩,经过长时间的循环最终还是会破裂;往电解液中加入添加剂这一策略操作简单,可适应目前已有的商业化钠电生产流程和设备,但往往这类添加剂是消耗性的,会随着电池循环次数的增长而慢慢变少;固态电解质由于其固有的安全特性和抑制钠枝晶生长的潜力而被认为非常具有发展前景,不过目前固态电解质电池还无法有效解决离子电导率低和界面阻抗大的问题;合金化负极可以有效抑制钠枝晶的形成,可是缺点也很明显,即额外引入的没有活性的金属成分会大大增加电极的质量,从而降低能量密度;结构化负极可以在多个方面改善钠金属负极的性能,前提是它要具有良好的机械性能,并且几乎所有结构化的负极都面临金属钠和电解液严重的副反应

Benefits of technology

[0034]1.通过采用本发明的技术方案,利用β相聚偏氟乙烯-六氟丙烯和芳香聚酰亚胺形成的多孔的三维骨架结构作为载体,将金属钠沉积在三维骨架结构中,可以大大缓解钠金属沉积和剥离过程中产生的体积变化,通过多孔的三维骨架结构具有的高比表面积的特性来减小局部电流,使得钠更均匀地沉积。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116613279B_ABST
    Figure CN116613279B_ABST
Patent Text Reader

Abstract

The application provides a metal sodium negative electrode, a preparation method thereof and a battery. The metal sodium negative electrode comprises a current collector; a three-dimensional network organic skeleton layer is loaded on the current collector; metal sodium is loaded inside the three-dimensional network organic skeleton layer; the three-dimensional network organic skeleton layer is formed by coating a polymer composite material and then drying; and the metal sodium is uniformly deposited inside the three-dimensional composite organic skeleton layer through a deposition process. By using the technical scheme of the application, the porous three-dimensional skeleton structure formed by beta-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is used as a carrier, the metal sodium is deposited in the three-dimensional skeleton structure, the volume change generated in the sodium metal deposition and stripping process can be greatly relieved, the high specific surface area characteristics of the porous three-dimensional skeleton structure are used to reduce the local current, and the sodium is more uniformly deposited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, specifically to a sodium metal anode, its preparation method, and a battery. Background Technology

[0002] With the increasing depletion of fossil fuels and the rapid development of clean energy sources such as wind and solar power, the global energy consumption pattern will gradually shift from fossil fuels to new energy sources. Sodium is abundant, widely distributed, and inexpensive on Earth, making sodium-ion batteries a promising large-scale energy storage solution that has attracted widespread attention from researchers both domestically and internationally. Metallic sodium possesses physicochemical properties similar to metallic lithium. + The standard electrode potential of the Na / N pair (-2.71 V, vs. NHE) is higher than that of the Li / N pair. + The voltage difference between sodium and Li is only 0.3V higher. Drawing on experience in lithium-ion battery electrode material research can significantly accelerate the development of sodium-ion battery electrode materials. However, the low energy density of sodium-ion batteries limits their applications, and sodium metal anodes have attracted considerable attention from researchers due to their extremely high theoretical specific capacity (1166 mAh / g). In particular, using sodium metal as the anode is prone to dendrite growth, which leads to low coulombic efficiency, poor cycle stability, and in severe cases, even battery fires and explosions, seriously hindering the development of sodium metal batteries. The current strategies for solving the sodium metal anode problem are as follows: (1) Design a uniform and stable artificial solid electrolyte interface (SEI) to replace the non-uniform and fragile native SEI film, thereby achieving uniform sodium deposition; (2) Develop efficient electrolyte additives to promote uniform sodium deposition or help the surface of active materials to generate a uniform and flexible SEI film; (3) Use high modulus solid electrolytes to suppress the growth of sodium dendrites and improve the coulombic efficiency of the battery; (4) Use sodium alloys to replace sodium metal to achieve dendrite-free anodes; (5) Construct novel structured sodium metal anodes through nanotechnology to regulate the deposition / stripping behavior of sodium ions and reduce the volume change of the electrode during repeated cycling.

[0003] The aforementioned strategies for improving the performance of sodium metal anodes each have their advantages and disadvantages. For example, sodium metal anodes modified with artificial SEI films show almost no reduction in energy density, but their strength is generally insufficient to resist the endless expansion / contraction of the electrode volume, and they will eventually break after long-term cycling. Adding additives to the electrolyte is a simple strategy that can be adapted to existing commercial sodium battery production processes and equipment, but these additives are often consumable and will gradually decrease as the number of battery cycles increases. Solid electrolytes are considered very promising due to their inherent safety characteristics and potential to inhibit sodium dendrite growth, but currently, solid electrolyte batteries cannot effectively solve the problems of low ionic conductivity and high interfacial impedance. Alloyed anodes can effectively inhibit the formation of sodium dendrites, but the disadvantages are also obvious: the additional inactive metal components will greatly increase the mass of the electrode, thereby reducing the energy density. Structured anodes can improve the performance of sodium metal anodes in several aspects, provided that they have good mechanical properties, and almost all structured anodes face serious side reactions between metallic sodium and the electrolyte. Existing technologies also employ two or more strategies in combination in batteries to achieve superior performance in all aspects. However, the combined use of multiple strategies increases the complexity of the process and raises manufacturing costs, making it uneconomical.

[0004] The performance of negative electrode materials can be improved by using polymer materials with three-dimensional network structures as carriers for uniform metal deposition, thereby enhancing the electrical performance of batteries. For example, Chinese invention patent CN114335550A discloses a method for preparing a three-dimensional organic framework composite material, which constructs a three-dimensional network structure formed by polymer nanofibers on the surface of the current collector, achieving uniform lithium deposition. However, this three-dimensional network structure is prepared by electrospinning, which requires additional equipment and processes, increasing manufacturing costs and reducing production efficiency, thus hindering large-scale promotion and production. Chinese invention patent CN108232117A discloses a lithium metal negative electrode, which obtains a three-dimensional framework lithium carrier by tightly attaching melamine foam to the current collector, achieving uniform lithium deposition. However, this method has very weak or even almost no adhesion between the current collector and the framework material, which is not conducive to the preparation of other types of batteries besides coin cells, and also hinders the performance of the battery. Furthermore, the pore size of the three-dimensional structure is not adjustable, and the thickness is difficult to control. In addition, a single framework structure cannot simultaneously meet the requirements of mechanical strength, electrochemical performance, and other aspects.

[0005] Therefore, based on the existing publicly available technologies, developing a sodium metal anode material that can take into account both mechanical and electrochemical properties and has a simple preparation method is of great significance for advancing the performance of actual sodium-ion batteries. Summary of the Invention

[0006] This invention discloses a sodium metal anode, its preparation method, and a battery. A polymer is coated on the surface of the current collector to form a three-dimensional framework structure. The operation method is simple, requires no other auxiliary equipment, and the resulting carrier structure is stable, providing good mechanical strength for the sodium anode material. This greatly reduces the process flow and saves manufacturing costs.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a sodium metal anode, comprising a current collector; a three-dimensional network organic framework layer is loaded on the current collector; and sodium metal is loaded inside the three-dimensional network organic framework layer.

[0008] The three-dimensional network organic framework layer is formed by coating with a polymer composite material and then drying it.

[0009] Sodium metal is uniformly deposited inside the three-dimensional network organic framework layer using an electrodeposition process.

[0010] Preferably, the polymer composite material comprises polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide. Polyvinylidene fluoride and polyimide are both polar crystalline polymers. According to the principle of like dissolves like, polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide can form a homogeneous composite system of polyvinylidene fluoride-hexafluoropropylene-aromatic polyimide.

[0011] Preferably, the polymer composite material is dissolved in a solvent to form a slurry, and the slurry is coated onto the surface of the current collector by a coating method. After drying, the three-dimensional network organic framework layer is obtained.

[0012] Preferably, the mass ratio of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is 1:5 to 5:1.

[0013] Preferably, the solvent is a mixture of acetone and water; the mass ratio of the two is 5:1 to 10:1; wherein, acetone acts as a solvent to dissolve the polymer, and water acts as a pore-forming agent and plays a role in phase separation.

[0014] Preferably, the mass of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide accounts for 5 to 20% of the total mass of the slurry.

[0015] Preferably, the current collector is an aluminum foil or a copper foil.

[0016] Preferably, the polyvinylidene fluoride in polyvinylidene fluoride-hexafluoropropylene is a β-crystalline phase. The β-crystalline phase has the highest polarization and can interact with sodium ions, which is beneficial for the deposition of sodium metal.

[0017] Preferably, the molecular weight of polyvinylidene fluoride-hexafluoropropylene is 300,000-800,000, and the molecular weight of aromatic polyimide is 50,000-300,000. The appropriate molecular weight is an important factor in forming a high-performance skeleton. If the molecular weight is too small, there will be less entanglement between molecular chains and insufficient tensile strength. If the molecular weight is too large, it will be difficult to dissolve and the viscosity will be too high while the solid content will be low, which is not conducive to the preparation process.

[0018] To achieve another objective, the present invention also provides a method for preparing the above-mentioned sodium metal anode, comprising the following steps:

[0019] S1. Preparation of slurry: Polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide are added to a mixed solution of acetone and water, and stirred at 55°C for 4 hours to obtain slurry;

[0020] S2. Coating: The slurry obtained in S1 is coated onto the surface of the current collector by a coating method, and then dried so that the slurry adheres tightly to the surface of the current collector;

[0021] S3. Drying: The current collector coated with slurry is dried until the solvent residue on the surface is completely removed. The slurry forms a three-dimensional composite organic framework layer on the surface of the current collector, thus obtaining the negative electrode sheet.

[0022] S5. Using the electrode obtained in step (4) as the working electrode and the sodium metal sheet as the counter electrode, the electrode is immersed in an electroplating tank containing electrolyte under an inert atmosphere. The sodium on the sodium metal sheet is deposited onto the three-dimensional composite organic framework by an electrodeposition process to obtain the sodium metal negative electrode.

[0023] Preferably, in step S2, the current collector coated with slurry is first placed in a room temperature drying environment for natural drying, and then placed in an oven for further drying.

[0024] Preferably, in S3, the thickness of the negative electrode sheet is 1–25 μm.

[0025] Preferably, in step S4, the electrodeposition process conditions include a current density of 0.2–20 mAh / cm³. 2 The total charging time should be controlled between 0.02 and 20 hours. If the current density is too low, the electrodeposition process will take too long, affecting production efficiency. If the current density is too high, the electrodeposition will be uneven, affecting the performance of the electrode and even causing sodium dendrites, creating safety hazards. At a suitable current density, if the total charging time is too short, too little sodium metal will be deposited, which is detrimental to cycle life. If the total charging time is too long, too much sodium metal will be deposited, increasing costs.

[0026] Preferably, the electrodeposition process conditions include a current density of 5–10 mAh / cm³. 2 .

[0027] More preferably, the current density is 5 mAh / cm³. 2 .

[0028] Preferably, the negative electrode sheet serves as the working electrode, and the sodium metal sheet serves as the counter electrode. Under a helium atmosphere, the electrode is immersed in an electroplating bath containing an electrolyte solution, which is a mixed solution of NaPF6 and EC / PC / EMC. Film-forming additives are added, and sodium on the sodium metal sheet is deposited onto the three-dimensional composite organic framework through an electrodeposition process.

[0029] Preferably, in the electrolyte, the concentration of NaPF6 in the mixed solvent of EC / PC / EMC is 1 mol / L; the volume ratio of EC / PC / EMC is 1:3:6.

[0030] Preferably, the film-forming additive is 1.0% by mass of fluoroethylene carbonate (FEC), manufactured by Huzhou Kunlun Yienke Battery Materials Co., Ltd.

[0031] When the sodium anode described above is assembled with another identical sodium metal anode to form a battery pair, the polarization voltage of the sodium metal anode is not higher than 12mV; when the battery is assembled with a NaNiFeMn cathode as a full cell, the battery cycle life (80% BOL) is greater than 380 cycles.

[0032] This invention utilizes the unilateral arrangement of fluorine atoms in the highly polar β-phase polyvinylidene fluoride-hexafluoropropylene (PVDF-HFA) molecular chain to enhance the interaction between the highly electronegative CF functional groups and sodium, inducing uniform sodium deposition. Meanwhile, polyimide possesses excellent mechanical properties and tensile strength, capable of withstanding the stress during frequent sodium deposition / peeling processes on the framework. In particular, the interaction between the polar CF functional groups on the PVDF-HFA molecular chain and the polar carbonyl and amine groups on the aromatic polyimide molecular chain contributes to improving the mechanical strength of the framework. The interacting polar functional groups form clusters with sodium ions through electrostatic interactions, regulating the sodium ion flux in the electrolyte and inducing uniform sodium ion dispersion and deposition. Based on these principles, the composite framework sodium metal anode prepared using these two materials not only possesses the advantages of both materials but also, through synergistic effects, provides excellent electrochemical and mechanical performance for both the sodium anode and the battery.

[0033] Technical effects of the present invention:

[0034] 1. By adopting the technical solution of the present invention, a porous three-dimensional framework structure formed by β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is used as a carrier to deposit metallic sodium in the three-dimensional framework structure. This can greatly alleviate the volume change generated during the sodium metal deposition and stripping process. The high specific surface area of ​​the porous three-dimensional framework structure reduces the local current, making the sodium deposit more uniformly.

[0035] 2. By adopting the technical solution of the present invention, a non-conductive polymer three-dimensional framework structure is used, which avoids the problem of sodium dendrites being generated by direct deposition of sodium on the framework compared with a conductive framework.

[0036] 3. The technical solution of the present invention directly uses a coating method to coat the polymer onto the surface of the current collector to form a three-dimensional skeleton structure. The operation method is simple, requires no other auxiliary equipment, and the resulting carrier structure is stable, providing good mechanical strength for the sodium anode material. This greatly reduces the process flow and saves manufacturing costs. In particular, the preparation method of the three-dimensional skeleton provided by the present invention is simple, compatible with existing sodium battery production equipment and processes, and the preparation process of the three-dimensional skeleton does not require additional investment, making it suitable for large-scale production.

[0037] 4. By adopting the technical solution of this invention, the highly polar β-phase polyvinylidene fluoride-hexafluoropropylene has a good interaction with sodium ions in the electrolyte. The polar functional groups on its surface can regulate the sodium ion flux in the electrolyte and uniformly distribute sodium ions. The unilateral arrangement of fluorine atoms in the β-phase polyvinylidene fluoride-hexafluoropropylene can enhance the interaction force between the highly electronegative CF functional groups and sodium, inducing uniform sodium deposition. Polyimide has good mechanical properties and high tensile strength, and can better withstand the stress generated during the deposition / peeling process of sodium on the skeleton, thus enhancing the mechanical strength of the skeleton. The sodium metal anode made with the composite skeleton has excellent electrochemical and mechanical properties, and the sodium metal battery composed of it has lower polarization and longer cycle life. Attached Figure Description

[0038] Figure 1 A comparison diagram of the polarization voltage curves of Embodiment 1, Comparative Example 1, Comparative Example 3 and Comparative Example 5 of the present invention.

[0039] Figure 2 A comparison graph of the cycle performance curves of Example 2, Comparative Example 2, Comparative Example 4 and Comparative Example 6 of the present invention. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0041] This invention provides a sodium metal anode, comprising a current collector; a three-dimensional network organic framework layer coated with a composite material of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is loaded on the current collector; sodium metal is loaded inside the three-dimensional network organic framework layer; wherein, the sodium metal is uniformly deposited inside the three-dimensional composite organic framework layer by a deposition process.

[0042] The polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide composite material is prepared by dissolving polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide in an organic solvent to form a slurry, which is then coated onto the surface of a current collector and dried to form a three-dimensional network organic framework layer.

[0043] The mass of polyvinylidene fluoride-hexafluoropropylene is m1, the mass of aromatic polyimide is m2, the mass of propylene is m3, the mass of water is m4, and the total mass of the solution is M; wherein m1+m2 accounts for 5%-20% of the total mass of the solution, m3+m4 accounts for 80%-95% of the total mass of the solution, m1∶m2=1∶5~5∶1, m3∶m4=5∶1~10∶1. If the proportion of m1+m2 is less than 5%, the resulting framework is too loose and may not even be able to form a framework structure. If the proportion of m1+m2 is higher than 30%, it cannot be completely dissolved, and the solution viscosity is too high, which is not conducive to the preparation process. The ratio of m1:m2 should also be controlled within a suitable range. If one component is too much or too little, it cannot play its full role, and the synergistic effect will be greatly weakened. The ratio of m1:m2 should be controlled between 1:5 and 5:1. The ratio of m3:m4 should also be controlled within a suitable range. If there is too much water, the pore size of the framework structure is prone to be uneven, and the pore size is too large, which is not conducive to uniform sodium deposition. If there is too little water, it is not conducive to the formation of a porous structure. The ratio of m3:m4 should be controlled between 5:1 and 10:1.

[0044] The technical solution of the present invention will be further described in detail below through specific embodiments.

[0045] Example 1

[0046] This embodiment provides a sodium metal anode, the preparation steps of which include:

[0047] (1) Add β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide to a mixed solution of acetone and water, and stir at 55°C for 4 hours to obtain a viscous solution as a slurry; wherein, in the slurry, the mass ratio of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is 1:5; the mass ratio of acetone and water is 5:1; wherein, polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide account for 15% of the total mass of the solution.

[0048] (2) Transfer the slurry obtained in step (1) to a coating machine and coat the slurry onto the surface of the aluminum foil current collector by coating method; the total thickness of the aluminum foil current collector is 10 μm;

[0049] (3) Place the aluminum foil current collector obtained after coating in step (2) in a room temperature dry environment for 3 hours until the solvent has basically evaporated, and a three-dimensional network organic skeleton layer of composite material closely attached to the current collector can be obtained.

[0050] (4) Place the pre-dried aluminum foil current collector from step (3) in an 85°C oven and bake for 12 hours to completely remove the solvent remaining in the three-dimensional network organic framework layer, thus obtaining the negative electrode sheet.

[0051] (5) Using the negative electrode obtained in step (4) as the working electrode and the sodium metal sheet as the counter electrode, the electrode is immersed in an electroplating bath containing an electrolyte (or named L-1 electrolyte) under a helium atmosphere. The electrolyte (or L-1 electrolyte) is a mixed solution of 1M NaPF6 and EC / PC / EMC in a volume ratio of 1:3:6, with 1.0% FEC added as a film-forming additive. The manufacturer is Huzhou Kunlun Yienke Battery Materials Co., Ltd. (hereinafter referred to as L-1 electrolyte). Sodium on the sodium metal sheet is deposited onto the three-dimensional composite organic framework through an electrodeposition process. In the electrodeposition process, the current density is 10 mAh / cm³. 2 Charge for 10 hours; after electrodeposition, a sodium metal anode is obtained.

[0052] The sodium metal anode prepared in this embodiment was assembled with another identical sodium metal anode to form a battery pair, with L-1 electrolyte, and electrochemical tests were performed.

[0053] Example 2

[0054] The preparation steps of this embodiment are exactly the same as those of the sodium metal anode in Example 1.

[0055] The only difference is that the sodium metal anode prepared in Example 1 was assembled with the NaNiFeMn cathode into a full cell, and the electrochemical performance was tested.

[0056] Example 3

[0057] The only difference between this embodiment and Example 1 is that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide in step (1) is 1:1.

[0058] Example 4

[0059] The preparation steps of this embodiment are exactly the same as those of the sodium metal anode in Example 3.

[0060] The only difference is that the sodium metal anode prepared in Example 3 was assembled with the NaNiFeMn cathode into a full cell, and the electrochemical performance was tested.

[0061] Example 5

[0062] The only difference between this embodiment and Example 1 is that the mass ratio of acetone to water in step (1) is 10:1.

[0063] Example 6

[0064] The preparation steps of this embodiment are exactly the same as those of the sodium metal anode in Example 5.

[0065] The only difference is that the sodium metal anode prepared in Example 5 was assembled with the NaNiFeMn cathode into a full cell, and the electrochemical performance was tested.

[0066] Example 7

[0067] The only difference between this embodiment and Embodiment 1 is that the electrodeposition process current density in step (5) is 5 mAh / cm³. 2 It takes 20 hours to charge.

[0068] Example 8

[0069] The preparation steps of this embodiment are exactly the same as those of the sodium metal anode in Example 7.

[0070] The only difference is that the sodium metal anode prepared in Example 7 was assembled with the NaNiFeMn cathode into a full cell, and the electrochemical performance was tested.

[0071] Comparative Example 1

[0072] The only difference between this comparative example and Example 1 is that in step (1), only polyvinylidene fluoride-hexafluoropropylene is used to prepare the slurry, without adding aromatic polyimide.

[0073] The sodium metal anode obtained in this comparative example was assembled into a battery with another identical sodium metal anode, and electrochemical tests were performed.

[0074] Comparative Example 2

[0075] The only difference between this comparative example and Example 1 is that in step (1), only polyvinylidene fluoride-hexafluoropropylene is used to prepare the slurry, without adding aromatic polyimide.

[0076] The sodium metal anode obtained in this comparative example was assembled with a NaNiFeMn cathode into a full cell, and electrochemical tests were performed.

[0077] Comparative Example 3

[0078] The only difference between this comparative example and Example 1 is that in step (1), only aromatic polyimide is used to prepare the slurry, without adding polyvinylidene fluoride-hexafluoropropylene.

[0079] The sodium metal anode obtained in this comparative example was assembled into a battery with another identical sodium metal anode, and electrochemical tests were performed.

[0080] Comparative Example 4

[0081] The only difference between this comparative example and Example 1 is that in step (1), only aromatic polyimide is used to prepare the slurry, without adding polyvinylidene fluoride-hexafluoropropylene.

[0082] The sodium metal anode obtained in this comparative example was assembled with a NaNiFeMn cathode into a full cell, and electrochemical tests were performed.

[0083] Comparative Example 5

[0084] In this comparative example, two identical sodium-plated aluminum foil negative electrodes were assembled to form a battery, and electrochemical tests were performed.

[0085] The preparation method of the sodium-plated aluminum foil negative electrode includes: directly electrodepositing metallic sodium on the aluminum foil, with the specific process conditions being the same as the preparation step (5) in Example 1.

[0086] Comparative Example 6

[0087] In this comparative example, full cells assembled with sodium-plated aluminum foil anode and NaNiFeMn cathode were used for electrochemical testing.

[0088] The preparation method of sodium-plated aluminum foil negative electrode includes: directly electrodepositing metallic sodium on aluminum foil, with specific process conditions the same as preparation step (5) in Example 1.

[0089] Comparative Example 7

[0090] The only difference between this comparative example and Example 1 is that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide in step (1) is 1:10.

[0091] The sodium metal anode obtained in this comparative example was assembled into a battery with another identical sodium metal anode, and electrochemical tests were performed.

[0092] Comparative Example 8

[0093] The only difference between this comparative example and Example 1 is that the mass ratio of polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide in step (1) is 1:10.

[0094] The sodium metal anode obtained in this comparative example was assembled with the NaNiFeMn cathode into a full cell, and electrochemical tests were performed.

[0095] Comparative Example 9

[0096] The only difference between this comparative example and Example 1 is that the mass ratio of acetone to water in step (1) is 3:1.

[0097] The sodium metal anode obtained in this comparative example was assembled into a battery with another identical sodium metal anode, and electrochemical tests were performed.

[0098] Comparative Example 10

[0099] The only difference between this comparative example and Example 1 is that the mass ratio of acetone to water in step (1) is 3:1.

[0100] The sodium metal anode obtained in this comparative example was assembled with the NaNiFeMn cathode into a full cell, and electrochemical tests were performed.

[0101] Comparative Example 11

[0102] The only difference between this comparative example and Example 1 is that in step (1), polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide account for 3% of the total mass of the solution.

[0103] The sodium metal anode obtained in this comparative example was assembled into a battery with another identical sodium metal anode, and electrochemical tests were performed.

[0104] Comparative Example 12

[0105] The only difference between this comparative example and Example 1 is that in step (1), polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide account for 3% of the total mass of the solution.

[0106] The sodium metal anode obtained in this comparative example was assembled with the NaNiFeMn cathode into a full cell, and electrochemical tests were performed.

[0107] Refer to Table 1 for a comparison of the electrochemical performance of Examples 1-8 and Comparative Examples 1-12.

[0108] Table 1 compares the electrochemical performance of Examples 1-8 and Comparative Examples 1-12.

[0109]

[0110]

[0111] In Comparative Examples 1-4, the preparation methods of the polyvinylidene fluoride-hexafluoropropylene backbone sodium metal anode and the aromatic polyimide backbone sodium metal anode were the same as those in the Example Group, except that only a single polymer material (polyvinylidene fluoride-hexafluoropropylene or aromatic polyimide) was added in preparation step (1). As can be seen from the comparison of electrochemical performance in Table 1, compared with the control group battery, the polarization voltage of the battery in the embodiment of the present invention was significantly reduced, and the cycle life was significantly improved.

[0112] See Figure 1The figures show a comparison of the polarization voltage curves of Example 1, Comparative Example 1, Comparative Example 3, and Comparative Example 5. The electrolyte used is L-1 electrolyte. The curves show that among the four types of batteries composed of negative electrodes, the composite skeleton (Example 1) battery has the lowest polarization voltage, and the polarization voltage does not show an increasing trend during the process, which is significantly better than the other three types of negative electrodes.

[0113] See Figure 2 The figures show a comparison of the cycle performance curves of Example 2, Comparative Example 2, Comparative Example 4, and Comparative Example 6, with L-1 electrolyte. The curves show that the composite skeleton negative electrode (Example 2) has a higher cycle life.

[0114] Referring again to Table 1, by comparing Examples 2, 4, and 6 with Example 8, Example 8 is the best example, when the sodium plating current density is 5 mAh / cm². 2 At that time, it has the highest cycle life.

[0115] By comparing Examples 1, 3, and 5 with Example 7, Example 7 is the best example, when the sodium plating current density is 5 mAh / cm². 2 At this point, the polarization voltage is lowest. In summary, the sodium plating current density is 5 mAh / cm². 2 Sodium anode materials prepared by depositing sodium onto a framework structure can produce better electrochemical and cycle performance of batteries.

[0116] Furthermore, Comparative Examples 7 and 8 tested battery performance under a polyvinylidene fluoride:polyimide mass ratio of 1:10; Comparative Examples 9 and 10 tested battery performance under an acetone:water mass ratio of 3:1; and Comparative Examples 11 and 12 tested battery performance under a polyvinylidene fluoride:polyimide addition of 3%. The test results in Table 1 clearly show that the ratio of m1 to m2 should be controlled between 1:5 and 5:1, and the ratio of m3 to m4 should also be controlled within a suitable range. If there is too much water, the pore size of the framework structure is prone to becoming uneven, and the pore size is too large, which is not conducive to uniform sodium deposition. If there is too little water, it is not conducive to the formation of a porous structure. The ratio of m3 to m4 should be controlled between 5:1 and 10:1.

[0117] The above are merely preferred embodiments of the present invention and do not limit the scope of protection of the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any changes, modifications, substitutions, integrations, and parameter alterations to these embodiments within the spirit and principles of the present invention, achieved through conventional substitutions or by achieving the same function without departing from the principles and spirit of the present invention, fall within the scope of protection of the present invention.

Claims

1. A sodium metal anode, comprising a current collector; a three-dimensional network organic framework layer loaded on the current collector; and sodium metal loaded inside the three-dimensional network organic framework layer; in, The three-dimensional network organic framework layer is formed by coating with a polymer composite material and then drying it. Sodium metal is uniformly deposited inside the three-dimensional network organic framework layer through a deposition process. The polymer composite material is dissolved in a solvent to obtain a slurry; the slurry is coated onto the surface of the current collector by a coating method, and then dried to obtain the three-dimensional network organic framework layer. The polymer composite material comprises β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide; the β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide form a homogeneous composite system; The mass ratio of β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide is 1:5~5:1; The solvent is a mixture of acetone and water; the mass ratio of the two is 5:1 to 10:

1. The β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide account for 5-20% of the total mass of the slurry.

2. The sodium metal anode according to claim 1, characterized in that, The current collector is made of aluminum foil or copper foil.

3. A method for preparing a metallic sodium anode as described in any one of claims 1-2, characterized in that, Includes the following steps: S1. Preparation of slurry: β-phase polyvinylidene fluoride-hexafluoropropylene and aromatic polyimide are added to a mixed solvent of acetone and water, and stirred at 55°C for 4 hours to obtain slurry; S2. Coating: The slurry obtained in S1 is coated onto the surface of the current collector by a coating method, and then dried so that the slurry adheres tightly to the surface of the current collector; S3. Drying: The current collector coated with slurry is dried until the solvent residue on the surface is completely removed. The slurry forms a three-dimensional composite organic framework layer on the surface of the current collector, thus obtaining the negative electrode sheet. S4. Using the negative electrode obtained in S3 as the working electrode and the sodium metal sheet as the counter electrode, the electrode is immersed in an electroplating tank containing electrolyte under an inert atmosphere. The sodium on the sodium metal sheet is deposited onto the three-dimensional composite organic framework through an electrodeposition process to obtain the sodium metal negative electrode.

4. The method for preparing a sodium metal anode according to claim 3, characterized in that, In step S2, the current collector coated with slurry is first placed in a room temperature drying environment to dry naturally; then it is placed in an oven to dry again.

5. The method for preparing a sodium metal anode according to claim 3, characterized in that, In S3, the thickness of the negative electrode sheet is 1~25μm.

6. The method for preparing a sodium metal anode according to claim 3, characterized in that, In S4, the electrodeposition process conditions include a current density of 0.2~20 mAh / cm³. 2 The total charging time is controlled between 0.02 and 20 hours.

7. The method for preparing a sodium metal anode according to claim 3, characterized in that, In S4, the inert atmosphere is helium.

8. The method for preparing a sodium metal anode according to claim 3, characterized in that, In S4, the electrodeposition process conditions include a current density of 5~10 mAh / cm³. 2 .

9. The method for preparing a sodium metal anode according to claim 3, characterized in that, In S4, the electrodeposition process conditions include a current density of 5 mAh / cm³. 2 .

10. The method for preparing a sodium metal anode according to claim 3, characterized in that, The negative electrode sheet serves as the working electrode, and the sodium metal sheet serves as the counter electrode. Under a helium atmosphere, the electrodes are immersed in an electroplating bath containing an electrolyte solution, which is a mixture of NaPF6 and EC / PC / EMC. Film-forming additives are added, and sodium from the sodium metal sheet is deposited onto the three-dimensional composite organic framework through an electrodeposition process.

11. The method for preparing a sodium metal anode according to claim 10, characterized in that, In the electrolyte, the concentration of NaPF6 in the mixed solvent of EC / PC / EMC is 1 mol / L; the volume ratio of EC / PC / EMC is 1:3:

6.

12. The method for preparing a sodium metal anode according to claim 10, characterized in that, The film-forming additive is FEC with a mass percentage concentration of 1.0%.

13. A battery comprising a metallic sodium negative electrode as described in any one of claims 1-2.

Citation Information

Patent Citations

  • Preparation method of three-dimensional organic framework composite material, lithium metal negative electrode and battery

    CN114335550A

  • Anode material for lithium metal battery as well as preparation method and application of anode material

    CN108232117A

  • Sodium metal negative electrode protective layer, sodium metal negative electrode and preparation method and application thereof

    CN112531145A

  • Nonaqueous electrolytic secondary battery

    JP1997129240A